Conceptual Study on Problems in Network Optimization and Routing in Communication Networks: Exploring the ties between linear programming and combinatorial optimization in network optimization and routing (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Network optimization lies amidst the immense gap that isolates the two noteworthy kinds of optimization problems, consistent and discrete. The ties between linear programming and combinatorial optimization can be followed to the representation of the imperative polyhedron as the convex frame of its outrageous focuses. At the point when a network is included, in any case, these ties turn out to be significantly more grounded in light of the fact that the extraordinary purposes of the polyhedron are number and represent solutions of combinatorial problems that are apparently irrelevant to linear programming. As a result of this structure and furthermore as a result of their instinctive character, network models give ideal vehicles to clarifying a large number of the key thoughts in both ceaseless and discrete optimization. In this Research study we studied about the Problems in Network Optimization and Routing in Communication Networks in detail.